Occupational Health Hazards in Municipal Solid Waste Collecting Workers of Chandrapur City, Central India - Patil, Priyanka V.; Kamble, R. K. (International Journal of Environment, 2017)
Solid waste management has important occupational health issues associated with it. Out of 204 solid waste collecting workers of Chandrapur Municipal Corporation, 20 workers were selected (10% of the population) as sample size (15 female and 5 male) and 10 individuals as control group (5 female and 5 male). The study was carried out from November 2015 to January 2016. Peak Expiratory Flow Rate analysis was carried out through Breath-o meter and identification and assessment of other occupational health hazards through interview schedule specially designed and developed for this study. The results of the study showed that, Peak Expiratory Flow Rate values were lower in exposed workers as compared with control group. These workers were exposed to a number of environmental and occupational hazards leading to musculoskeletal disorders (100%), respiratory problems (90%), headache (90%), dermatological problems (25%) and gastrointestinal problems (15%) during work. It was further observed that these workers were suffering from allergies (100%), stomach pain (50%), asthma and bronchitis lungs (45%), cough and cold (25%), vomiting (25%), hearing disorder (20%), fever (15%), typhoid (10%), malaria (5%) etc. after completion of work.INTERNATIONAL JOURNAL OF ENVIRONMENT, Volume-6, Issue-1, Dec-Feb 2016/17, page: 46-57